Evaluating the efficacy of probiotics in treating Parkinson’s disease model rats using magnetic resonance enhanced gradient echo T2-weighted angiography sequence - Su, Yanmin; Dong, Yanchao; Feng, Jingtao; Zhang, Xiaoxia; Yu, Ying; Lu, Hongzhi (Frontiers in Neuroscience, 2025)
BackgroundParkinson’s disease (PD) involves iron deposition in the substantia nigra (SN) and loss of dopaminergic neurons, with gut microbiota dysbiosis potentially affecting the brain iron via the gut–brain axis, whereas magnetic resonance enhanced gradient echo T2-weighted angiography (ESWAN) enables non-invasive iron assessment. Currently, for the detection of brain iron content, traditional tissue biopsy can provide accurate pathological information. However, its clinical and scientific research applications are limited owing to its invasiveness, difficulty in repeated operations, and other limitations. This study aimed to evaluate the therapeutic efficacy of probiotics and underlying mechanisms in PD rats using ESWAN.MethodsTwenty-seven male Sprague–Dawley rats were divided into control, PD model, and probiotic treatment groups. PD models were established by 6-hydroxydopamine stereotaxic injection into the SN, whereas the treatment group received oral gavage of Lactobacillus acidophilus and Bifidobacterium bifidum mixture. ESWAN was used to quantify iron deposition, complemented by iron histochemical staining and wire grip tests for motor function assessment.ResultsThe probiotic treatment significantly reduced right SN R2* values (p < 0.0001) and iron staining optical density (p < 0.0001), and prolonged the time of wire grip duration (p < 0.0001) compared with PD rats, though not fully to control levels. Mechanistically, probiotics likely alleviated iron overload via gut–brain axis modulation, antioxidant enzyme enhancement, and blood–brain barrier maintenance. The strong positive correlation (r ≥ 0.7) between ESWAN-derived R2* values and iron staining confirmed ESWAN as a reliable non-invasive tool for brain iron assessment.ConclusionThis study provides experimental evidence that probiotics mitigate SN iron deposition in PD rats by regulating gut microbiota, highlighting ESWAN as a potential imaging biomarker for early PD diagnosis and therapeutic monitoring.